Business risk and sales on the value of manufacture companies with capital structure as intervening variables in stock exchange - Setyowulan, Rika; Isnurhadi, Isnurhadi; Widiyanti, Marlina; Adam, Mohamad (International research journal of management, IT and social sciences, 2020)
This study aimed to determine the effect of business risk, sales growth on firm value with capital structure as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. To be able to understand this aim, we have reviewed 20 company's profiles and report from 2015 to 2018 with a purposive sampling technique. After collected the needed data, then analyzed data using the technique of panel data regression and path analysis. Finally, we obtained that the capital structure has a significant positive effect on firm value, business risk. While sales growth does not affect firm value and business risk does not affect capital structure. Sales growth has a significant negative effect on capital structure. The capital structure is only able to mediate the effect of sales growth on the value of the company. This study has its validity and reliability and therefore, it can be useful insights to support infrastructure business and other policymakers as well as academic projects working on similar issues.